2021
DOI: 10.1021/acs.orglett.1c00714
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Resolution of Nearly Symmetric 3-Cyclohexene-1-carboxylate Esters Using a Bacterial Carboxylesterase Identified by Genome Mining

Abstract: A new bacterial carboxylesterase (CarEst3) was identified by genome mining and found to efficiently hydrolyze racemic methyl 3-cyclohexene-1-carboxylate (rac-CHCM) with a nearly symmetric structure for the synthesis of (S)-CHCM. CarEst3 displayed a high substrate tolerance and a stable catalytic performance. The enantioselective hydrolysis of 4.0 M (560 g•L −1 ) rac-CHCM was accomplished, yielding (S)-CHCM with a >99% ee, a substrate to catalyst ratio of 1400 g•g −1 , and a space-time yield of 538 g•L −1 •d −1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The intricate stereochemical structures of enzymes often manifest in distinctive spatial, hydrophobic, and electrostatic properties, particularly within the active center, forming the basis for high stereoselectivity [5][6][7] . However, enzymes face challenges maintaining high stereoselectivity, especially when confronted with substrates boasting nearly symmetric structures [8][9][10] . These substrates are commonly deemed "hard-to-bediscriminated," not only by chemical catalysts but also by biocatalysts 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…The intricate stereochemical structures of enzymes often manifest in distinctive spatial, hydrophobic, and electrostatic properties, particularly within the active center, forming the basis for high stereoselectivity [5][6][7] . However, enzymes face challenges maintaining high stereoselectivity, especially when confronted with substrates boasting nearly symmetric structures [8][9][10] . These substrates are commonly deemed "hard-to-bediscriminated," not only by chemical catalysts but also by biocatalysts 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…6 It has been reported that more than 2 or 3 recrystallization processes are required to afford the salt with high diastereoselectivity. Meanwhile, Tanyeli and Turkut, 7 and Xu, Ni, and co-workers 8 individually reported biotransformations from the racemic 3-cyclohexene-1-carboxylic acid methyl ester 2. In this chiral resolution strategy, generally, discarding at least half of the starting racemic mixture is inevitable.…”
Section: ■ Introductionmentioning
confidence: 99%